Expression, regulation and function of miR-126 in the mouse choroid vasculature. (May 2018) - Zhao, Fangkun; Anderson, Chastain; Karnes, Sara; Zhou, Qinbo; Ma, Jing; Jin, Zheng-Gen; Bhattacharjee, Partha S.; Wang, Shusheng
Abstract: MicroRNA miR-126 has been shown to be required for proper angiogenesis in several models. However, its expression, regulation and function in the mouse choroid remain unclear. Our previous data has shown that miR-126 expression is enriched in the endothelial cells (ECs) of the mouse choroid. Here we report that a 5.5 kb Egfl7/miR-126 promoter drives the expression of miR-126 in the choroid ECs during choroidal vascular development. The expression of miR-126 in the ECs is regulated by flow stress likely through Krüppel-like transcriptional factors. miR-126 −/− mice show mildly delayed choroidal vascular development, but adult knockout mice develop periphery choroidal vascular lesions. This study suggests that miR-126 is largely dispensable for mouse choroidal development but required for maintaining choroidal vasculature integrity. Highlights: microRNA miR-126 activity is detected and restricted to the choroidal endothelial cells (EC) during early choroid vascular development. The expression of miR-126 in the ECs is regulated by flow stress likely through transcription factor Krüppel-like factors. miR-126 −/− mice show mildly delayed choroidal vascular development, but the adult knockout mice develop peripheral choroidal vascular lesions.